Utilization of Digital Media in Building the Morals of High School Students of 11 Medan State High School - Nurmala Br Saragih; Ihsan Satrya Azhar (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to determine the use of digital media in fostering students' moral character at SMA Negeri 11 Medan and to identify its supporting and inhibiting factors. This research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results show that digital media is utilized in Islamic Religious Education through educational videos, online learning platforms, social media, and religious content that support students' moral development. The use of digital media can improve students' discipline, responsibility, and ethical behavior when applied properly and in a well-directed manner. The supporting factors include the availability of technological facilities, school support, and the active role of teachers in character building. Meanwhile, the inhibiting factors include lack of supervision and improper use of digital media by students. With proper guidance, digital media can be an effective tool in shaping better student character in the digital era.